PENGARUH INTENSITAS MENONTON LIVE STREAMING TIKTOK LIVE DAN PRODUCT KNOWLEDGE DI TIKTOK SHOP TERHADAP MINAT BELI GEN Z PADA PRODUK FASHION - Gabryella, Cathrine; Setyabudi, Djoko; Naryoso, Agus (Interaksi Online, 2024)
This research aims to explore the influence of watching TikTok live streaming intensity and product knowledge in TikTok Shop on Gen Z's purchase interest in fashion products. A questionnaire survey method was used to collect data from 100 respondents, using nonprobability sampling - purposive sampling, with specific criteria such as Gen Z (aged 13- 26 years) and having watched TikTok LIVE. Analysis using simple linear regression was employed to determine the relationship between variables of live streaming intensity and purchase interest, as well as product knowledge and purchase interest. The research findings indicate that the intensity of watching live streaming significantly affects consumer purchase interest on fashion products at TikTok Shop, while product knowledge does not affect purchase interest. These findings provide valuable insights for businesses in understanding consumer behavior, especially Gen Z, and implementing appropriate marketing strategies on the TikTok platform.